Death in paradise. Season two [videorecording (DVD)] - Miller, Ben, 1966-; Martins, Sara, 1977-; John-Jules, Danny (BBC Worldwide, 2013)
Detective Richard Poole is still trapped on the stunning Caribbean island of Saint Marie, but, for him, the sun, sea, and sand aren't quite paradise. Faced with puzzling murders and a local team with unorthodox approaches, Poole must use his eye for detail, relentless logic and stubborn refusal to leave anything unexplained to solve these cases. He is joined once again by the feisty Camille Bordey, instinctive, wild, exotic and brilliant. Together they face a pirate curse, murdered nuns and a case that must be solved while a hurricane bears down on the island.